(untitled) (Research, Society and Development, 2021)
Retrospective study, of mixed approach, with quantitative and qualitative approaches, with the objective of analyzing posts about non-suicidal self-harm on Twitter. The posts were collected through screen capture, transcribed and encoded. Quantitative data were analyzed using descriptive statistics, association tests and multiple logistic regression, with a significance level of 5%. Qualitative data were analyzed using thematic analysis by Braun and Clarke. In the results, female profile tweets and potentially harmful content prevailed. The expression of the suicidal behavior of the author of the post was associated with the encouragement of non-suicidal self-harm and increased chances of sharing and commenting on the posts. Reply posts were more likely to receive likes and comments. Posts encouraging non-suicidal self-harm describe social manifestations of behavior and exposure to non-suicidal self-harm through mass communication. The results bring important discussions about the potential impact of posts on non-suicidal self-harm and reflection on the discussion of behavior in the digital social context. It is important that mental health actions include tracking risk behaviors on the internet, supporting people in situations of vulnerability, redirecting to support services, as well as strategic actions to promote the conscious and healthy use of social networks.